(untitled) (American Journal of Islam and Society, 1995)
This is perhaps one of the most useful books I have come across in recent years. In an age when almost every Middle East or Islamic studies specialist is obsessed with "political Islam" or "radical or fundamentalist Islam," and when the western mass media and below-average media specialists on the Muslim world try to explain "the rage of Islam" to their audience, this book is a forceful reminder that the political language of contemporary Islamic revivalism is grounded in a historically established and rich Islamic (political) tradition. It also reminds us that in order to do justice to the political principles of the modem Islamic movement, both the academics and the media specialists must familiarize themselves with this rich and historically constructed tradition. The author’s primary intention is to document and discuss the main sources (i.e., writings) of Islamic political thought from the first centuries to the present. To ’Arif, the Islamic theory of knowledge and practice, which is based on the Qur’an and the Sunnah, has worked as a catalyst that enabled the Muslim mind to construct a unique political theory that takes into account changing sociopolitical and historical conditions. As a result, "political thought" has always formed the crux of Islamic thinking in general and has never been divorced from the unique evolution and progress of Islamic civilization. What this means, in effect, is that for a modem scholar to carry out research, let us say, on the concept of jihad in Islam, he/she must trace the concept to its earlier sources and study it in its epistemological and historical evolutions. Concepts do change, depending on ...